The Role of Yoga in Health and Wellness (Global Journal of Human-Social Science, 2015)
Modern life style is posing a series challenge to human health. The fast change of ever changing trends in modern life is causing physical, moral, mental, and spiritual problems. Chaos and confusion, stress and tension, commercialization and competition in every walk of life has lead to a situation where man is finding itself helpless regarding his personal health and hygiene. An individual who comes to this earth has every right to enjoy each and every gift of nature, to live freely and happily. Technological advancement has resulted in reduction of physical labour and increased mental labour. Tough labour in turn has resulted in psychosomatic disorders such as hyper tension, diabetes, insomnia acidity, gastric problems etc. Basically these disorders are caused due to faulty eating habits, stressful working conditions lack of physical exercises and proper rest. Yoga is the only possible remedy to counter these hazardous habits. Practice of yogic principals and virtues are the only means wherein an individual can make his life happy and free from miseries. Health and wellness is the concern of each and every person. The condition of modern life offers us much less in spite of our material wealth, than it did to the previous generations. We suffer from the modern disease-stress stress created by selfishness, competitiveness, acquisitiveness and insensitivity to the destruction of our human relations and environment. As a result we suffer from all sorts of physical and mental illness which evens our modern schools of medical science cannot alleviate. Instead, many people are turning to a far older tradition, a tradition that appears to be steeped in religion and mystery, but, in facts, are much more pragmatic in its application to our everyday lives than it would first appear. Yoga should not be considered as an antiquated myth of yesterday because it has as much validity and value now as it had ever before and can offer guidance and help to the modern man. There are
Keywords: yoga; health